Prediction of atomic structure of Pt-based bimetallic nanoalloys by using genetic algorithm - Oh, Jung Soo; Nam, Ho-Seok; Choi, Jung-Hae; Lee, Seung-Cheol (KOREAN INST METALS MATERIALS, 2013)
The atom-arrangements in Pt-based bimetallic nanoalloys were predicted by the combined use of genetic algorithm (GA) and molecular dynamics (MD) simulations. The nanoparticles of these nanoalloys were assumed to be a 3.5 nm-diameter truncated octahedron with Pt and noble metals of fixed composition ratio of 1:1. For the GA, a Python code, which concurrently linked with the MD method that uses the embedded atom method inter-atomic potentials, was developed for the prediction of the atom arrangements in these bimetallic nanoalloys. Successfully, the GA calculation predicted the core-shell structures for both Pt-Ag and Pt-Au nanoalloy, but an onion-like multilayered core-shell structure for Pt-Cu nanoalloy. The structural characteristics in the bimetallic nanoalloy were mainly due to the differences in the surface energy and cohesive energy between Pt and the other alloying metal elements and their miscibility gap and so on. Briefly, the prediction performance was analyzed to show the superior searching ability of GA.
Keywords: MOLECULAR-DYNAMICS SIMULATION; GOLD NANOCLUSTERS; GEOMETRY OPTIMIZATION; SURFACE SEGREGATION; AU CLUSTERS; NANOPARTICLES; STABILITY